Age of diagnosis of Duchenne muscular dystrophy in Peru 2023: a cross-sectional study - Martínez-Esteban, Peggy Carol (2023)
Background: Duchenne muscular dystrophy (DMD), a progressive neuromuscular disease, usually manifests before the age of 5. In low- and middle-income countries, diagnosis is often delayed compared with high-income countries. This difference in the diagnosis timing could influence the disease's management and prognosis. Objective: The study aimed to determine the age of diagnosis of DMD in Peruvian patients treated in a high-complexity hospital or belonging to independent associations. Methods: Descriptive study through a survey of patients diagnosed with DMD. Results: 95 patients were included with a mean age of 12.4 years (range 3-34). The mean age at diagnosis of DMD was 8.1 years (range 7 - 307 months); in patients younger than ten years, the mean age was 4.9 years, and in those older than ten years, the mean age was 9.7 years. The mean age of first attendance to the healthcare system for symptoms related to DMD was 43.34 months (range 5-216), and the most common symptoms that prompted were motor or gait difficulties and frequent falls. At the first consultation, 47.4% were seen by a pediatrician, who dismissed the symptoms in 44.4%, and only 11% requested creatine kinase. The mean time from first consultation to diagnosis was 4.4 years. Genetic indings included deletions in 46.3% of cases, duplications in 16.8%, and point mutations in 36.8%. Conclusions: The mean age of definitive diagnosis of DMD in Peruvian patients is 8.1 years, although the diagnosis tends to be made earlier in children under ten years of age. This suggests that the detection of DMD in Peru has improved in the last decade, leading to a timelier diagnosis.